Legal aspects of informed consent in clinical research: the case of vaccinations in the international legal framework (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Informed consent is an essential prerequisite in clinical trials. The goal of the informed consent process is to provide appropriate information, so that the potential participant can make an informed decision about whether or not to enrol in a trial. Information must concern the explanation of the research status, its objectives, a description of benefits and risks, alternative treatment that may be available, and the subject's rights and responsibilities. After a review of the main regulatory instruments on informed consent, the article analyses the EU regulatory framework for vaccines. In a second part, the issue of voluntariness and validity of informed consent in case of compulsory vaccination is discussed, through an examination of selected national rules (France, Spain, Italy, and Germany).
Keywords: Informed consent; clinical trials; law; vaccines; public health and human rights